Castro and Franco : the backstage of Cold War diplomacy - Hosoda, Haruko (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Cuba's Fidel Castro and Spain's Francisco Franco were two men with very similar backgrounds, but very different political ideologies. Both received a catholic education and had strong connections to the Galicia region of Spain. Both were familiar with guerrilla tactics and came to power through fighting civil wars. However, Franco had support from fascists, who fought a vicious campaign against communist guerrillas, whereas Cuba was strategically aligned with the USSR after the Revolution. The two countries nevertheless maintained strong relations, notably keeping a formal diplomatic relationship after the 1959 Cuban Revolution despite the US's severing of ties to Cuba. This relationship, Hosoda argues, would remain a vital back channel for communication between Cuba and the West. Using a mixture of primary and secondary sources, derived from the Cuban, American and Spanish archives, Hosoda analyses the nature and wider role of diplomatic relations between Cuba and Spain during the Cold War. Addressing both the question of how this relationship was forged--whether through the personal strange 'amity' of their leaders, mutual animosity towards the US, or the alignment of national interests--and the importance of the role that it played. Considering also the role of the Vatican, this book offers a fascinating insight into a rarely studied aspect of the Cold War, one which transcends the usual East-West binaries"--
Galicia's influence : Castro and Franco's common roots -- Consequences of the Spanish Civil War : revolutionary Cuba and Castro -- Catholicism as a life line during the Cold War : independent Spanish diplomacy toward Castro's Cuba -- Anti-Americanism in Cuba and Spain and American prejudice -- People fighting for a cause vs. pragmatists -- The reconciliation of generations : the post-Franco era and Castro -- Conclusion: Everything changes : who leaves his name in history?
OCLC-licensed vendor bibliographic record.
Keywords: Castro, Fidel, -- 1926-2016 -- Political and social views; Franco, Francisco, -- 1892-1975 -- Political and social views; Cuba -- Foreign relations -- Spain; Spain -- Foreign relations -- Cuba; Cold War -- Diplomatic history; POLITICAL SCIENCE / Government / International; POLITICAL SCIENCE / International Relations / General